ASXL1 gene alterations in patients with isolated 20q deletion - Březinová, Jana; Šárová, Iveta; Svobodová, Karla; Lhotská, Halka; Ransdorfová, Šárka; Izáková, Silvia; Pavlištová, Lenka; Lizcová, Libuše; Skipalova, K; Hodaňová, Lucie; Marková, Jana; Zemanová, Zuzana; et al. (Neoplasma, 2019)
Deletion 20q is a recurrent abnormality in myeloid malignancies. In our previous study, we identified fusion of the additional sex combs-like 1 (ASXL1) and teashirt zinc finger homeobox 2 genes in a patient with myelodysplastic syndrome. The objective of this study was to determine the frequency of ASXL1 breakpoints in a cohort of 36 patients with deletion 20q as the sole cytogenetic aberration. A combination of molecular cytogenetic methods was used to confirm ASXL1 gene alterations in 19 of the 36 patients, and the determination of ASXL1 gene changes in patients with deletion 20q revealed clinical and prognostic impacts.
Keywords: chromozomální delece; cytogenetické vyšetření; lidské chromozomy, pár 20; Myelodysplastic Syndromes; Chromosomes, Human, Pair 20; lidé; myelodysplastické syndromy; Repressor Proteins; Chromosome Deletion; Cytogenetic Analysis; represorové proteiny; Humans